Experiment study on the humidity control performance and indoor environment control of diatom ooze. (26th April 2018) - Yang, Hua; Wen, Qian-ying; Zhang, Xu-jun; Liu, Lian-sheng; Zhou, Ying
ABSTRACT: As an important indoor environment parameter, air humidity plays an important role in indoor health, thermal comfort and energy consumption of heating and air-conditioning. In this paper, the experimental study on the humidity control performance and the effect of humidity control in the practical application environment for diatom ooze were carried out. The micro – characterized of research object was carried out by low-temperature nitrogen adsorption-desorption, and the adsorption and desorption properties of diatomite and three kinds were studied, obtaining equilibrium moisture absorption and desorption curves, isothermal desorption and desorption rates, cyclic desorption and desorption properties. Based on the above results, it was concluded that the performance of diatom humidity control of three different construction processes. Then, the room temperature and humidity of three rooms were obtained by testing the indoor environment of diatom ooze room, latex paint room and wallpaper room in different seasons, compering and analyzing the effect of diatom ooze on the indoor thermal and humid environment. Results show that the pore structure characteristics and ambient temperature of diatom ooze have a great influence on its humidity control performance; the diatom ooze is more effective in winter and summer, and the transition season is weaker.